The Effect of NPK Fertilizer and Liquid Organic Fertilizer Made From Rice Washing Water on the Growth of Pakchoy (Brassica rapa L.) - Maulanda, Rezqi; Raksun, Ahmad; Mertha, I Gde (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Macronutrients (N, P, and K) are essential for plants. Plants that are deficient in any of these elements may produce less in terms of both quantity and quality. The purpose of this study is to ascertain how pakchoy (Brassica rapa L.) growth is impacted by the concentration of liquid organic fertilizer from rice washing water and NPK fertilizer. This study used a completely randomized design with two components and five treatment levels: liquid organic fertilizer treated with rice washing water (0 ml, 10 ml, 20 ml, 30 ml, and 40 ml) and NPK fertilizer treatment (0 g, 0.5 g, 1 g, 1.5 g, and 2 g). Anova was used to examine research data. The study's findings demonstrated that NPK fertilizer significantly impacted plant growth in terms of plant height, leaf area, number of leaves, and wet and dry weight. Plant height, the quantity of leaves, and plant wet weight were not significantly affected by rice-washed liquid organic fertilizer, but leaf area and dry weight were. The growth of pakchoy was not significantly impacted by the combination of liquid organic fertilizer from rice washing water and NPK fertilizer.